The military and domestic politics [ a concordance theory of civil-military relations - Schiff, Rebecca L. (Cass military studies, 2009)
Explains how concordance theory can provide a model for predicting domestic intervention. Using five case studies - India, Pakistan, Israel, Argentina, and Post-Revolutionary America - this book challenges traditional views on the role of the military in society, and offers examples for the continual application of concordance theory